Effect of n-butanol fumigation on the regulated and unregulated emission characteristics of a diesel engine. (15th April 2019) - Gowtham, M.; Mohan, C.G.; Prakash, R.
Highlights: Utilization of n-butanol for powering a diesel engine. N-butanol vapours are premixed along with air. Higher brake thermal efficiency was noticed with n-B20. Lower levels of nitric oxide and toxic emissions were noticed with n-B20. Abstract: Many investigations have been carried on the utilization of ethanol and methanol fuels in diesel engine to study the performance and regulated emission characteristics. However, very few investigations are made with discussion on the unregulated emissions. So the present work is focussed on the investigation of performance and emissions (both regulated and unregulated) from premixed n-butanol vapours in a single cylinder, four stroke, direct injection diesel engine and the results are presented in this paper. In this work n-butanol was used as a fuel owing to its longer-chain structure compared to methanol or ethanol, resulting in a lower specific heat of vaporization and greater enthalpy of combustion, while lowering water susceptibility and greater possibility than ethanol or methanol fuel. Subsequently, n-butanol has properties considerably closer to diesel fuel than ethanol, rendering it best to mix or fumigated with normal diesel fuel. In this work, n-butanol is fumigated along with the air in three different volume percentages such as 10, 20 and 30. About 14.76% higher brake thermal efficiency was noticed when 20% n-butanol was fumigated compared with the neat diesel operation. The oxides of nitrogen, acetaldehyde and acrolene emissions are reduced by 11.4%, 20.08% and 40.81% respectively. However, the HC, CO, formaldehyde and acetone emissions are increased with increased percentages of n-butanol.